GE_GERICHTE P/11500/2024 vom 23. Mai 2025 - GE Cour de justice (2025)
CIRCULATION À DROITE;CROISEMENT(EN GÉNÉRAL);FRAIS JUDICIAIRES;DÉPENS | LCR.34.al1; LCR.34.al4; LCR.35.al2; OCR.9.al1; OCR.9.al2; CPP.428; CPP.429.al1.letA